3D printing of normal and pathologic tricuspid valves from transthoracic 3D echocardiography data sets. (24th December 2016) - Muraru, Denisa; Veronesi, Federico; Maddalozzo, Anna; Dequal, Daniele; Frajhof, Leonardo; Rabischoffsky, Arnaldo; Iliceto, Sabino; Badano, Luigi P.
Abstract : Aims: To explore the feasibility of using transthoracic 3D echocardiography (3DTTE) data to generate 3D patient-specific models of tricuspid valve (TV). Methods and Results: Multi-beat 3D data sets of the TV (32 vol/s) were acquired in five subjects with various TV morphologies from the apical approach and analysed offline with custom-made software. Coordinates representing the annulus and the leaflets were imported into MeshLab (Visual Computing Lab ISTICNR) to develop solid models to be converted to stereolithographic file format and 3D print. Measurements of the TV annulus antero-posterior (AP) and medio-lateral (ML) diameters, perimeter (P), and TV tenting height (H) and volume (V) obtained from the 3D echo data set were compared with those performed on the 3D models using a caliper, a syringe and a millimeter tape. Antero-posterior (4.2 ± 0.2 cm vs. 4.2 ± 0 cm), ML (3.7 ± 0.2 cm vs. 3.6 ± 0.1 cm), P (12.6 ± 0.2 cm vs. 12.7 ± 0.1 cm), H (11.2 ± 2.1 mm vs. 10.8 ± 2.1 mm) and V (3.0 ± 0.6 ml vs. 2.8 ± 1.4 ml) were similar ( P  = NS for all) when measured on the 3D data set and the printed model. The two sets of measurements were highly correlated ( r  = 0.991). The mean absolute error (2D − 3D) for AP, ML, P and tenting H was 0.7 ± 0.3 mm, indicating accuracy of the 3D model of <1 mm. Conclusion: Three-dimensional printing of the TV from 3DTTE data is feasible with highly conserved fidelity. This technique has the potential for rapid integration into clinical practice to assist with decision-making, surgical planning, and teaching.